Canon EOS Rebel T3i/600D for dummies - King, Julie Adair. (--For dummies., 2011)
An introduction to the Canon EOS Rebel T3i/600D camera examines the purpose and function of the camera's basic controls and how to use them, accompanied by explanations of custom functions, choosing exposure settings, manipulating focus and color, and downloading pictures --